Job strain and burnout in Spanish nurses during the COVID-19: resilience as a protective factor in a cross-sectional study - María del Mar Molero Jurado; África Martos Martínez; María del Carmen Pérez-Fuentes; Héctor Castiñeira López; José Jesús Gázquez Linares (BMC, 2022)
Abstract Background Nurses are frequently exposed to chronic stress in the workplace generating harmful effects such as job strain and burnout. On the contrary, resilience has been shown to be a beneficial variable. The objective of this study was to analyze the relationship between dimensions of the Job Demand Control-Support model, resilience and burnout in nurses, and examine the mediating role of resilience between job strain and burnout. Methods A descriptive, cross-sectional study reported in line with the STROBE guidelines. Active nurses were invited to complete an online questionnaire in September, 2020. With snowball sampling, 1013 nurses, with a mean age of 34.71, filled out the Job Content Questionnaire, the Maslach Burnout Inventory and the Resilience Scale. Results The results showed the existence of four groups of professionals based on job strain. The nurses in the "High Strain" group (high demands and low control) showed higher scores in emotional exhaustion and cynicism, while those in the "Active Job" group scored higher in personal realization and resilience. The findings showed that job strain affects burnout in nurses, and this effect is mediated by resilience. Conclusions The findings of this study showed that a high level of resilience could exert a fundamental role in ensuring well-being and proper job performance by nurses. Nursing managers should see to the personable variables or competencies that provide and favor an opportunity for nurses to widen and improve their practice, in pursuance of satisfying and responding better to people's needs and the systems they work for.